Heavy quarkonium in the saturated environment of high-multiplicity pp collisions - Kopeliovich, Boris Z.; Pirner, Hans J.; Potashnikova, I. K.; Reygers, Klaus; Schmidt, Iván (Physical review, 2020)
High-multiplicity pp collisions exhibit features, traditionally associated with nuclear effects. Coherence motivates to treat high-multiplicity pp, pA, and AA collisions on an equal footing. We rely on the phenomenological parametrization for mean multiplicities of light hadrons and J/ψ, assuming their linear dependence on Ncoll in pA collisions. The results of this approach underestimate the recently measured production rate of J/ψ at very high hadronic multiplicities. The linear dependence of J/ψ multiplicity on Ncoll is subject to predicted nonlinear corrections, related to mutual boosting of the saturation scales in colliding dense parton clouds. A parameter-free calculation of the nonlinear corrections allows us to explain data for pT-integrated yield of J/ψ at high hadronic multiplicities. Calculations are in a good accord with data binned in several pT intervals as well. As was predicted, Υ and J/ψ are equally suppressed at forward rapidities in pA collisions. Consequently, their fractional multiplicities at forward rapidities in pp collisions are equal as well, and their magnitude agrees with data.
Gesehen am 21.04.2020